From Motivation to Organizational Identity of Members in Non-profit Organizations: The Role of Collectivism - Li, Yong; Zhang, Yuting (Frontiers in Psychology, 2020)
This study contributes to our understanding of organizational identity through dichotomous motivations of altruism and egoism in nonprofit organizations. By applying an empirical analysis of NPO members, organizational identity is found to be well explained by altruistic motivation and egoistic motivation. More importantly, this study finds that collectivism positively moderates the relationship between altruistic motivation and organizational identity, and negatively moderates the relationship between egoistic motivation and organizational identity. It is noticeable that altruistic motivations have a stronger impact on organizational identity when collectivism is high, while egoistic motivations have a stronger impact on organizational identity when collectivism is low. Finally, this study generates helpful management implications based on research findings. It is suggested that the managers of NPOs could enhance members’ organizational identity by taking motivations and collectivism into consideration, that is to say, in order to build up organizational identity of NPO members, both righteousness and shared interests matter simultaneously.